2012
DOI: 10.1002/bsl.2006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Accused Juvenile Sex Offenders in Germany: A Comparison of Five Different Measures

Abstract: The present study examines the relationship between risk and protective factors among young alleged sexual offenders (N = 66) in pre-trial and pre-treatment settings. For risk assessment purposes, the Screening Tool for the Assessment of Young Sexual Offenders' Risk (STAYSOR), the Structured Assessment of Violence Risk in Youth (SAVRY), and the Structured Assessment of Protective Factors for violence risk (SAPROF) were used. Psychopathological indicators measured with the Basis Raads Onderzoek (BARO) and the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
2
18
0
3
Order By: Relevance
“…Our results agree with those of prior studies (Welsh et al, 2008; Klein et al, 2012; Childs et al, 2014; Hilterman et al, 2014, 2016; Shepherd et al, 2014b). When comparing total and partial mean scores on the SAVRY instrument, the scores from this study are lower than those calculated in other research studies (Dolan and Rennie, 2008; Gammelgard et al, 2008; Lodewijks et al, 2008; Meyers and Schmidt, 2008; Hilterman et al, 2014, 2016; Shepherd et al, 2014a; Chu et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results agree with those of prior studies (Welsh et al, 2008; Klein et al, 2012; Childs et al, 2014; Hilterman et al, 2014, 2016; Shepherd et al, 2014b). When comparing total and partial mean scores on the SAVRY instrument, the scores from this study are lower than those calculated in other research studies (Dolan and Rennie, 2008; Gammelgard et al, 2008; Lodewijks et al, 2008; Meyers and Schmidt, 2008; Hilterman et al, 2014, 2016; Shepherd et al, 2014a; Chu et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…It represents another step forward in the study of instruments for predicting risk of recidivism. In particular, this study of the SAVRY supplies information that can be compared to other studies performed in this country and internationally (McEachran, 2001; Catchpole and Gretton, 2003; Borum et al, 2006; Dolan and Rennie, 2008; Duits et al, 2008; Gammelgard et al, 2008; Lodewijks et al, 2010; Vincent et al, 2011; Klein et al, 2012; Childs et al, 2013, 2014; Hilterman et al, 2014, 2016; Shepherd et al, 2014a; Chu et al, 2016), as well as information for carrying out systematic, meta-analysis reviews (Schwalbe, 2007, 2008; Olver et al, 2009; Fazel et al, 2012; Singh et al, 2013), and for future generalization studies focusing on the instrument’s reliability and validity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Spice et al (2013) assumed, therefore, that specific protective factors for sexual recidivism might potentially exist, which are different from those for general and violent recidivism. In a study examining the prevalence of protective factors in a sample of 66 young accused juveniles who sexually offended, also using parts of the sample assessed within the current study, Klein et al (2012) reported a negative correlation between protective factors measured by the Structured Assessment of PROtective Factors for violence risk (SAPROF;de Vogel et al, 2009), and the SAVRY risk factors. Furthermore, a negative relationship between protective factors and psychopathological problems was reported.…”
Section: Protective Factors In Juveniles Who Sexually Offendedmentioning
confidence: 91%